DIVERSIFIKASI PRODUK BANDENG JUNOK DAN PENDAMPINGAN SERTIFIKASI HALAL MENUJU PASAR MODERN - Mashudi, Mashudi; Nashrullah, Faiz; Vibriyanto, Norita (As-Sidanah, 2025)
This community service activity is titled: Product Innovation of the Junok Milkfish Basket Group: Diversification of processed milkfish and halal certification assistance towards the Modern Market, it is important to answer the Asta Cita of President Prabowo Subianto's government, namely economic development to encourage the nation's independence from dependence on other countries through self-sufficiency in food, energy, water, creative economy, green economy, and economy blue, as well as development centered on downstreaming and strengthening the village economy. The Junok Al-Barokah milkfish basket group faces two main problems: First, traditional marketing is carried out without clear branding. Second, the problem of Junok milkfish production capacity is not optimal due to a less strategic marketing system. The efforts to improve the competitiveness of milkfish products carried out in Junok are consistent with the results of several studies and community service activities conducted elsewhere, including in Keputih, Surabaya, and in Kendal district by previous community service providers. It shows that ontologically, the benefits of diversifying milkfish products are understood. However, epistemologically, how can diversification and halal certification be implemented in other areas (Junok village in Madura) that have abundant natural resources for milkfish ponds and milkfish products? It is a novelty because no volunteer from any university or institution in the area has ever done it. It is the gap that needs answers and solutions. Thus, on an axiological level, this PKM activity addresses the need to improve the economy of Junok village in Sreseh sub-district. The Service Methodology is carried out through 4 key stages: Socialization, Training, Technology Application, and Evaluation and Reporting. The result of Abdimas's activities is that Abdimas Partners understands the brand identity and attractive packaging for Junok milkfish products, which have been successfully maintained through halal certification. In addition, they can apply equipment and technology to diversify product variants and develop marketing. Based on the evaluation results, the marketing of Junok milkfish, with its 3 processed variants, has increased sales to an average of 460kg from 250kg before the implementation of the Abdimas program.